E-Commerce: Variable Moderation in Marketing Strategies on Purchasing Decisions - Nareswari, Ayu (Bulletin of Management and Business, 2024)
This comprehensive study delves into the intricate dynamics of marketing strategies and their influence on consumer purchasing behavior concerning UMKM Mak Epa Frozen in Lumajang City. With e-commerce emerging as a crucial moderating variable, this research adopts a quantitative approach, integrating both descriptive and causal analyses. By surveying 100 dedicated patrons of UMKM Mak Epa Frozen, meticulously collected data is subjected to rigorous scrutiny using the sophisticated Smart-PLS 4 software. The discerning findings reveal: (1) a robustly positive and consequential correlation between marketing strategies and consumer purchasing decisions, (2) notably, although e-commerce exhibits significant relevance, it does not appear to moderate the impact of marketing strategies on consumer purchasing behavior.